Makna Pluralisme Agama dan Relevansinya dalam Tradisi Sufi; Kajian atas Kepribadian Abu Mansur al-Halaj - Arroisi, Jarman; Sari, Novita (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
The study of wihhdtul adyan thoughts which is often identified with religious pluralism has recently attracted the attention of academics, researchers, and reviewers of religions. The issue of wihdatul adyan, by some parties forcibly tried to be juxtaposed and equated with the wihdatul wujud thought conceptualized by a Sufi figure such as al-Hallaj. This paper intends to examine the model and practice of Sufism in the person of Abu Mansur Al-Hallaj, who is referred to by some as the bearer of the idea of ​​religious pluralism. This paper is also qualitative research with a philosophical-theological approach and concludes that; First, Al-Hallaj is not the originator and bearer of the idea of ​​religious pluralism in Islam, this is supported by several opinions of Sufis about Al-Hallaj. Second, Al-Hallaj acknowledged that there are differences in religion, not equality of religions (read: all religions are true) because in his childhood he experienced religious diversity in his family environment. Third, the claim against Al-Hallaj as the originator or father of religious pluralism is an excessive and irresponsible title, because what Al-Hallaj did is not under the alleged claim. This study provides an understanding that wihdatul wujud which is identical to the person of Al-Hallaj is not the meaning of wihdatul adyan which is often referred to as religious pluralism as claimed by some academics.